Bilateral hand transplantation: Functional benefits assessment in five patients with a mean follow-up of 7.6 years (range 4–13 years). Issue 9 (September 2015) - Bernardon, Laurence; Gazarian, Aram; Petruzzo, Palmina; Packham, Tara; Guillot, Michel; Guigal, Vincent; Morelon, Emmanuel; Pan, Hua; Dubernard, Jean-Michel; Rizzo, Christophe; Feugier, Patrick; Streichenberger, Thibault; et al.
Summary Between January 2000 and July 2009, five adults who had suffered bilateral traumatic below-elbow amputations, received bilateral hand-forearm allografts performed by the Lyon team. We report the functional benefits achieved over a mean follow-up period of 7.6 years (range 4–13 years), up to December 31st, 2013. Clinical measurement is hampered by the lack of specific validated assessment tools, obliging us to use non-specific standardized evaluation means. Our assessment shows that the restoration of motion, strength, and sensibility are fair. Functional results (Carroll upper extremity function test, 400-point test, Activities of daily living) are good, as well as quality of life evaluation (RAND-36). Subjective and overall results explored with questionnaires – Disabilities of the Arm Shoulder and Hand (DASH), Hand Transplantation Score System (HTSS), are very good. Improvement was seen to continue during the first three years, and then tend to become stable. Continued efforts should be directed at designing comprehensive, condition-specific, reliable outcome measurement tools. Continuous monitoring and evaluation of patients is required to assess the long-term risk-benefit balance.